Keberterimaan Siswa Terhadap Penggunaan Pembelajaran Gabungan pada Pembelajaran Bahasa Inggris - Fadilla, Ivan (ENGLISH RESEARCH JOURNAL, 2024)
The purpose of the research was to analyzed the students acceptance of using Blended Learning that supported by WhatsApp messenger application for the students at eleventh grade students in one of senior high schools in Central Java 2023/2024 academic year. The research was descriptive qualitative method. The subject of this research was the students of XI-F4 with 30 students. The data were collected by interviewing to the teacher and questionnaires to the students. To analyze the data, the researcher used qualitative data. Based on the research findings, learning English with the Blended Learning method that supported by WhatsApp messenger application has a significant impact on both the teacher and the learners. According to the questionnaires, utilizing WhatsApp messenger to learning English can help learners and make the learning process more enjoyable. Make communication and interaction between students and teacher easier without any limitation to time or space, so it can save the time and energy. It also revealed that students felt an improvement in their English skills and allow them to be more active and creative while using WhatsApp messenger application. Keywords: Students Acceptance, Blended Learning, WhatsApp messenger, Application.